Low frequency friction induced vibration of automotive disc brake - Magaswaran, Kumaresan (2014)
The automotive disc brake low frequency vibration has been a major concern in warranty issues and a challenging problem for many years. A variety of tools have been developed which include both experimental studies and numerical modeling technique to tackle the problem. The aim of this project is to develop a validated mathematical model considering the dynamic friction characteristics in the vibration of the disc brake. A key issue in the process is to investigate the structural deformation of the brake due to the friction distribution at the pad and disc contact during a typical braking cycle. A new methodology is introduced whereby the Green's equation is utilized to deduce the motion of the brake pad during braking. An experimental investigation using a brake dynamometer is also carried out to measure the vibration characteristics which are then used to validate the results predicted by the mathematical modeling. It is demonstrated that the mathematical model enhances the understanding of the time dependent non-linear contact behavior at the friction interface. The model was able to correspond to the frequencies of each modes obtained from the experiment with an average of 5 %. This, model in tum, demonstrated the fugitive nature of brake pad oscillation that appears and disappears as a function of friction distribution throughout the braking period. Parametric studies on the pressure and speed effects determine the contribution of each of these factors to brake pad leading end and trailing end behavior. The effects of these parameters were found to be modal depend, the decrease in speed during braking gave rise to vibration at frequencies between 500 Hz to 700 Hz where else braking at higher pressures subdued the vibration frequencies between 650 Hz to 850 Hz. Thus this approach can be used as a study tool to evaluate disc brake low frequency vibration using the mathematical model.